2007
DOI: 10.1097/01.mcg.0000225642.90898.0e
|View full text |Cite
|
Sign up to set email alerts
|

Both Plasma Lysophosphatidic Acid and Serum Autotaxin Levels are Increased in Chronic Hepatitis C

Abstract: The serum ATX activity and plasma LPA level are increased in chronic hepatitis C in association with liver fibrosis. Our study may provide the first evidence showing a significant increase of both ATX and LPA in the blood under a specific disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
133
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(151 citation statements)
references
References 41 publications
17
133
0
1
Order By: Relevance
“…However, there is a growing range of recognized chemical forms of LPA in various biological systems (31,32) that have been observed in concentrations spanning low nanomolar to micromolar levels. LPA concentrations in blood can range from 0.1 M in plasma and up to 10 M in serum, which is well over the apparent nanomolar K d of LPA [1][2][3][4][5][6] (23,(33)(34)(35) (36)(37)(38). Aside from blood, LPA has been quantifi ed in a variety of species, tissues, and fl uids, including neural tissue, cerebrospinal fl uid (CSF), seminal fl uid, urine, saliva, and aqueous humor (7,36,(39)(40)(41)(42)(43)(44)(45) (Table 1).…”
Section: Atxmentioning
confidence: 85%
See 1 more Smart Citation
“…However, there is a growing range of recognized chemical forms of LPA in various biological systems (31,32) that have been observed in concentrations spanning low nanomolar to micromolar levels. LPA concentrations in blood can range from 0.1 M in plasma and up to 10 M in serum, which is well over the apparent nanomolar K d of LPA [1][2][3][4][5][6] (23,(33)(34)(35) (36)(37)(38). Aside from blood, LPA has been quantifi ed in a variety of species, tissues, and fl uids, including neural tissue, cerebrospinal fl uid (CSF), seminal fl uid, urine, saliva, and aqueous humor (7,36,(39)(40)(41)(42)(43)(44)(45) (Table 1).…”
Section: Atxmentioning
confidence: 85%
“…are increased following hepatitis C-induced liver fi brosis, presumably through induction of stellate cell and hepatocyte proliferation (35,249), which are the main contributors to extracellular matrix accumulation in the liver (250).…”
Section: Reproductive System and Infertilitymentioning
confidence: 99%
“…Finally, the significance of the plasma or serum ATX levels in cancer patients has been reported in patients with follicular lymphoma, where serum ATX levels proved to be significantly higher than those in healthy subjects, to correlate with plasma LPA levels and to change according to patient clinical course (Masuda et al, 2008). Additional studies have reported an impressive and specific increase in serum ATX activity and plasma LPA in patients with chronic hepatitis C (Watanabe et al, 2007) and pancreatic cancer (Nakai et al, 2011). In the last 20 years several studies have considered the potential role of the ATX/LPA axis in ovarian cancer.…”
Section: Functionsmentioning
confidence: 95%
“…We read with interest the recent article by Marques et al 1 on the release of damage-associated molecular patterns during acetaminophen (APAP) hepatotoxicity in mice and humans. We were pleased to learn that the authors were able to confirm certain previously published data, especially the release of mitochondrial products in human pathophysiology, which we recently reported.…”
Section: Pathophysiological Relevance Of Neutrophils In Acetaminophenmentioning
confidence: 99%
“…2 However, we have concerns regarding the conclusion that neutrophils are aggravating APAP-induced hepatotoxicity based on the data presented. 1 Pretreatment with the neutropenia-inducing antibody Gr-1 induces a preconditioning effect with up-regulation of numerous genes, many of which are highly protective against APAP hepatotoxicity. 3 Thus, no reliable conclusions regarding the involvement of neutrophils can be obtained from these experiments.…”
Section: Pathophysiological Relevance Of Neutrophils In Acetaminophenmentioning
confidence: 99%